2000
DOI: 10.1071/ea00010
|View full text |Cite
|
Sign up to set email alerts
|

A field method for statewide ground-truthing of a spatial pasture growth model

Abstract: This paper describes an innovative method, commonly referred to as ‘spider mapping’, that allows pasture biomass and related data to be collected over large areas in a timely and efficient manner. Spider mapping was developed initially to collect data to allow calibration and validation of a spatial and temporal pasture growth model operating across Queensland on a 5 km grid basis. Two field officers made over 220 000 estimates and collected about 1300 samples of pasture biomass between January 1994 and August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Aussie-GRASS produces 5 × 5 km spatial simulations of the GRASP (grass production) pasture growth model (Hasset et al, 2000). The model uses daily inputs of climatic conditions (rainfall, temperature, solar radiation, evaporation, etc.…”
Section: Australian Land Erodibility Modelmentioning
confidence: 99%
“…Aussie-GRASS produces 5 × 5 km spatial simulations of the GRASP (grass production) pasture growth model (Hasset et al, 2000). The model uses daily inputs of climatic conditions (rainfall, temperature, solar radiation, evaporation, etc.…”
Section: Australian Land Erodibility Modelmentioning
confidence: 99%
“…In a pasture area in Queensland, Australia, a relatively high correlation between vegetation cover or canopy cover and vegetation indices with a coefficient of determination in excess of 0.9 has been reported (Hassett et al, 2000). This report utilized time series of satellite images and adopted the spider mapping method.…”
Section: Introductionmentioning
confidence: 99%
“…Tree Basal Area (m 2 ha −1 ) 0 -12 Hassett et al 2000). For the exclosure studies, GRASP was shown to account for a high proportion (r 2 =0.84 to 0.97) of both within-year and between-year variation in pasture yields over 5 years across five sites near Gayndah ( Fig.…”
Section: Treesmentioning
confidence: 94%